2019
DOI: 10.15275/rusomj.2019.0304
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of air pollution by small-sized suspended particulate matter in urbanized territories with various technogenic load (on the example of Vladivostok, Russia)

Abstract: The aim of the study was to estimate the pollution of the atmospheric surface layer by suspended particulate matter (SPM) in two districts of Vladivostok with different levels of technogenic load. Material and Methods -The air samples were taken in the "breathing zone" by an electric aspirator simultaneously to the liquid absorbing medium and on the filter, laser granulometry was used to assess the dispersion, and the mass concentration of the SPM fractions was calculated.Results -Ultrafine particles were dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…The contents of SPM of the air in the atmospheric surface layer in the districts of Vladivostok [28] with varying degrees of man-made load is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The contents of SPM of the air in the atmospheric surface layer in the districts of Vladivostok [28] with varying degrees of man-made load is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…The contents of SPM of the air in the atmospheric surface layer in the districts of Vladivostok [28] with varying degrees of man-made load is shown in Figure 1. It was revealed that the concentration of ultrafine particles (0-0.1 µm) in the area with a significant man-made load was 0.6 (0; 5.5) µg/m 3 and that of 0.1-1 µm particles was 1.5 (0; 6.7) µg/m 3 .…”
Section: Resultsmentioning
confidence: 99%
“…Atmospheric particulate matter (APM) in the air consists of many toxic pollutants (organic carbon species and alkanes, metals, sulfates, nitrates, etc.) [4,5]. Usually, APM is subdivided into particles with an aerodynamic diameter of up to 1 µm (PM1), 2.5 µm (PM2.5) and 10 µm (PM10) [6].…”
mentioning
confidence: 99%